2004
DOI: 10.1002/jnr.20280
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide detoxification by brain cells

Abstract: Peroxides are generated continuously in cells that consume oxygen. Among the different peroxides, hydrogen peroxide is the molecule that is formed in highest quantities. In addition, organic hydroperoxides are synthesized as products of cellular metabolism. Generation and disposal of peroxides is a very important process in the human brain, because cells of this organ consume 20% of the oxygen used by the body. To prevent cellular accumulation of peroxides and damage generated by peroxide-derived radicals, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
258
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(271 citation statements)
references
References 64 publications
8
258
0
5
Order By: Relevance
“…37 These results suggest that rotenone exposure enhanced the levels of pro-oxidative and antioxidative enzymes in glial cells. In addition, 24 hours after exposure to rotenone, the levels of glutathione (ie, GSH), a prominent antioxidant, were higher in rotenone-treated microglia than in mocktreated cells ( Figure 5C).…”
Section: Microglia Actively Respond To Rotenonetriggered Oxidative Stmentioning
confidence: 86%
See 1 more Smart Citation
“…37 These results suggest that rotenone exposure enhanced the levels of pro-oxidative and antioxidative enzymes in glial cells. In addition, 24 hours after exposure to rotenone, the levels of glutathione (ie, GSH), a prominent antioxidant, were higher in rotenone-treated microglia than in mocktreated cells ( Figure 5C).…”
Section: Microglia Actively Respond To Rotenonetriggered Oxidative Stmentioning
confidence: 86%
“…Unlike neurons, exposure to rotenone was not toxic to microglia, in either the presence or the absence of neurons; however, rotenone-treated microglia adopted a distinct activated form, indicating that microglia could actively respond to rotenone exposure. Studies 37,47 have shown that activated microglia release numerous inflammatory mediators, such as NO and superoxide, and produce antioxidants to successfully defend the CNS against threats to the brain. Microglia are equipped with efficient antioxidative defense mechanisms to prevent oxidative damage that would compromise their function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GPx and CAT participate in the elimination of H 2 O 2 , which is one of the most toxic molecules in the brain. Because GPx and CAT both control H 2 O 2 , they represent the major defense against ROS [14]. Decreased activity of Mn-SOD is a likely consequence of peroxynitrite after TBI, and could lead to further oxidative stress and progressively enhance peroxynitrite production as part of the secondary damage cascade [10].…”
Section: Discussionmentioning
confidence: 99%
“…and H 2 O 2 crosses the normal threshold, the system becomes compromised. Catalase and glutathione peroxidase (GPx), acting in concert with superoxide dismutase (SOD), constitute the major defense enzymes against superoxide radicals [13,14]. Analysis of these antioxidants, products of LPO and protein damage, may a yield snapshot of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is regarded as a factor contributing to inducement of the PTP and apoptosis [35,37,38]. Cells have antioxidant tools to degrade ROS, including SOD, catalase, glutathione peroxidase, and thioredoxins [39][40][41][42]. In many cases, it is still under debate whether ROS are the cause or consequence of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%